Pervasive theatre : New writing for new environments - Smith, Sophy (Convergence: The International Journal of Research into New Media Technologies, 2018)
This article explores the opportunities and implications for new digital writing in transmedia performance environments. This article centres on the experimental Pervasive Theatre project ( Assault Events 2014, commissioned by futuredream funded through Arts Council England), which explored the potential of online social tools to create a multimedia, collaborative and participatory work situated across multiple platforms. This project brought together researchers, artists, writers, technologists and practitioners from the interdisciplinary fields of digital writing, transmedia and performance to explore ways to develop narratives that weave together physical and online worlds, blurring the distinction between reality and fantasy, audience and performers in a way that would be exciting, immersive and participative. The project looked at different performative spaces including Facebook, Twitter, YouTube and Vines, exploring how these platforms could support the delivery of original narrative performance. This transmedia approach informed and shaped the digital writing practice, instigating new modes of working. Four aspects were of particular interest and will be explored in this article – how new writing can emerge from within online spaces rather than being translated onto them; how characteristics of different online social platforms inform style and content; how social media platforms can be used to develop narrative and character through creative collaboration with performers; and finally, how online social spaces enable the digital writer to develop a narrative framework through which audiences frame their own meaning.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzU0ODU2NTE2Njc1MjUz